Collision-Free Configuration Control of Spacecraft Systems Using Relative Measurements - Xia, Kewei; Zhang, Yiming; Wang, Wei; Zou, Yao; Zuo, Zongyu (IEEE transactions on aerospace and electronic systems, 2025)
This article investigates a distributed control strategy for the safety configuration of spacecraft systems subject to parameter uncertainty. The main feature lies in that the proposed control strategy is designed by directly using the local and relative measurements rather than the absolute information with its exchange via a communication device. To facilitate this design, the attitude and position dynamics are expressed in each local body frame. A distributed hybrid control torque is first developed such that the global stabilization without unwinding is guaranteed, where a data-based adaptive algorithm is introduced for the accurate identification of inertia parameters. Then, a distributed adaptive control force is proposed such that the relative configuration is ensured. In addition, a control barrier function (CBF) is exploited to optimize the control force to achieve the safety maneuver in the sense of collision avoidance and velocity constraint, where a cascade-filter-based relative velocity estimator is developed due to lack of relative velocity measurement. Stability analysis indicates that the closed-loop systems are uniformly asymptotically stable. Finally, simulation results verify the proposed strategy.